Trends and Factors Influencing the Length, Compensatory Growth, and Size‐Selective Mortality of Juvenile Bristol Bay, Alaska, Sockeye Salmon at Sea. Issue 1 (5th July 2016) - Yasumiishi, Ellen M.; Farley, Ed V.; Ruggerone, Gregory T.; Agler, Beverly A.; Wilson, Lorna I.
Abstract: The productivity of Bristol Bay, Alaska, Sockeye Salmon Oncorhynchus nerka increased during the mid‐1970s. This increase is believed to be partially due to an increase in early marine growth associated with the 1976–1977 cool‐to‐warm shift in summer sea surface temperature (SST). The body size of juvenile salmon during their first year at sea is believed to regulate their ability to survive over winter. The back‐calculated smolt length, first‐year ocean growth, and total juvenile length of Sockeye Salmon from five Bristol Bay river systems (Egegik, Kvichak, Naknek, Ugashik, and Wood) and two smolt ages were used to examine trends and factors influencing total juvenile length, compensatory growth, and size‐selective mortality in the first year in the ocean from 1962 to 2007. Juvenile length increased in relation to summer sea temperature, the 1977–2001 and 2002–2007 warm temperature regimes, smolt length, and compensatory growth. Compensatory growth—an inverse relationship between first‐year ocean growth and smolt size—increased over time as well as after the 1976–1977 climate regime shift, was more common in age‐1.0 fish than in age‐2.0 juveniles, and was important in determining the length of juvenile Sockeye Salmon from the Wood River (the shorter fish among rivers and smolt ages). The coefficient of variation in length did not change with SST, suggesting that size‐selective mortality occurred prior to the end of the first year at sea for all 10 fish groups. The predictor variables that were significant in the models varied among river systems and smolt ages. This study demonstrated that the frequency of compensatory growth and the total lengths of juvenile Sockeye Salmon during their first year at sea increased with summer SST (range, 7.5–10.5°C) in the eastern Bering Sea, a possible mechanism for the increased productivity of Bristol Bay Sockeye Salmon associated with warmer sea temperatures. Received June 2, 2015; accepted February 23, 2016